POLITIK HUKUM PENERAPAN PRESIDENTIAL THRESHOLD TERHADAP HAK-HAK PARTAI POLITIK DI INDONESIA (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
ABSTRACTThe application of the Presidential Threshold in Law Number 7 of 2017 concerning General Elections creates contradictions in the administration of politics in Indonesia. The rights of small political parties are stunted because they have to from coalitions with big parties. Political parties that should bridge the relationship between citizen and the government have turned into intermediaries for political interest. With a threshold, it will give birth to the political interest of parties supporting the government, the people will not get the desired candidate, thus triggering public apathy, and the big political parties will dominate. The purpose of this study to analyze the legal politics of implementing the Presidential Threshold on the rights of political parties in Indonesia. The research method used is normative research with a statutory and conceptual approach. The result show that the implementation of the Presidential Threshold will harm the goals of democracy and the spirit of reform because it eliminates the rights of political parties guaranteed in the 1945 Constitution, namely the meaning of recognition, guarantee of equal protection and certainty before the law because proposing candidates for election participants must form a coalition with large party with a fairly expensive cost. The legal politics of implementing the Presidential Thershold gave birth to an authoritarian political configuration because the government’s role was very dominant and political parties did not function properly because it would become a tool to justify the government’s will that gave birth to a political oligarchy. Keywords: Law political, Presidential Threshold, Political Party.ABSTRAK Penerapan Presidential Threshold dalam Undang-Undang Nomor 7 Tahun 2017 Tentang Pemilihan Umum menimbulkan kontradiksi dalam penyelenggaraan politik di Indonesia. Hak-hak partai politik kecil mengalami pengkerdilan karena harus berkoalisi dengan partai besar. Partai politik yang seharusnya menjembatani hubungan antara warga negara dengan pemerintah berubah menjadi perantara kepentingan-kepentingan politik. Dengan ambang batas akan melahirkan kepentingan politik partai pendukung pemerintah, rakyat tidak mendapatkan calon yang diinginkan sehingga memicu sikap apatisme masyarakat, dan partai politik besar akan mendominasi. Tujuan penelitian ini adalah untuk menganalisis politik hukum penerapan Presidential Threshold terhadap hak-hak partai politik di Indonesia. Metode penelitian yang digunakan adalah penelitian normative dengan pendekatan peraturan perundang-undangan dan pendekatan konseptual. Hasil penelitian menunjukkan bahwa penerapan Presidential Threshold akan menciderai tujuan demokrasi dan semangat reformasi karena menghilangkan hak partai politik yang dijamin dalam Undang-Undang Dasar Tahun 1945 yaitu makna pengakuan, jaminan perlindungan dan kepastian yang sama di muka hukum karena mengajukan calon peserta pemilu harus melakukan koalisi dengan partai besar dengan biaya yang terbilang mahal. Politik hukum penerapan Presidential Threshold melahirkan konfigurasi politik otoriter karena peran pemerintah sangat dominan dan partai politik tidak berfungsi dengan baik karena akan menjadi alat justifikasi kehenda pemerintah yang melahirkan oligarki politik.Kata kunci: Politik Hukum, Presidential Threshold, Partai Politik